FROM IMAGE TO THOUGHT THROUGH GEOMETRY AND COMICS: (iconic tools in teaching philosophy: theoretical framework, the possibilities of application, examples) - Milanković, Aleksandar (Metodička teorija i praksa, 2024)
How to bring abstract philosophical concepts and their relations in proximity with everyday, concrete pupils’ experience and spontaneous concepts? What factors can effectively and meaningfully mediate between usual perception and experience and abstract philosophical concepts,especially in the initial stages of teaching and learning, when pupils are introduced to philosophical problems? In accordance with these questions, the paper examines the meaning and possibilities of applying iconic tools or visual and graphic representations in the teaching of philosophy as intermediate elements that can connect complex, abstract philosophical concepts and theories with everyday experience and with the domain of phenomena and objects given in the immediate perception. First, the general theoretical foundations are explored, then possible directions of application, then a characteristic and valuable example already designed and adopted in teaching practice, and finally concluding considerations and proposals are made. The paper focuses on two specific groups of iconic tools: geometric (and geometrized) visuals and graphics and comics as a visual-graphic representation: we explore the foundations of their value in teaching and learning. Our conclusion is that iconic tools in teaching philosophy, if they are applied in a pedagogically and psychologically justified manner, if meaningful, relevant and aligned with the objectives of philosophy teaching and curriculum, have a great potential as an important intermediate factor for the gradual movement towards higher levels of abstraction, while preserving the transfer between philosophy and other subjects, as well as between philosophy and pupils' life experiences. In addition, their application can deepen cross-curricular connections, as well as a more intensive integration of teaching philosophy with key competencies and cross-curricular competencies.